A new species of the flower fly genus Criorhina Meigen (Diptera: Syrphidae) from mainland China - Li, Hu; Huo, Ke-Ke; Li, Bao-Guo (Zootaxa, 2020)
The genus Criorhina consists of honey-bee and bumblebee mimic flower flies with a strongly produced face. It is widespread in the Holarctic and Oriental Regions. Criorhina adults are usually found flying near white spring flowers in woodlands and shrubs. The Chinese Criorhina fauna is poorly known and includes seven species. In our flower fly collection of Henan Province, northern China, an eighth new species was discovered: Criorhina rostrata Li, Huo & Li sp. nov. This new species is here described and illustrated. The new species possess a very long proboscis, unique amongst the Criorhina species from mainland China. In addition, during the course of this study, Criorhina brevipila Loew, 1871 was also found to be present in mainland China, based on a specimen from our collection. A key to the species of Criorhina from mainland China is given.